1990
DOI: 10.2183/pjab.66.37
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of rice black-streaked dwarf virus genome segment 10.

Abstract: Plant reoviruses have segmented genomes consisting of 10-12 dsRNAs. They have been classified into subgroups 1, 2 and 3 based on vector species, particle morphology, and number of segmented genome. 7) Genome structure of wound tumor virus (WTV) genome segments 4-12 and rice dwarf virus (RDV) genome segments 9 and 10 have been determined.'~-4).s~,15).1`f2') From these studies, RDV and wTV, both belong to the same subgroup 1, have been shown to have some structural features in common. For example, both RDV and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…1). These data showed that the 5' and 3' termini of the plus strands of all segments are adenine and cytidine, respectively, because the 3' termini of the plus strand of genome segments S 10 Uyeda et al, 1990), $8 and $7 (data not shown) were identified as cytidine by cDNA analysis. The nucleotide sequences of terminal regions of the genome were analysed by the wandering spot method (de Wachter & Fiers, 1972;Rensing & Schoenmarkers, 1973) after partial alkaline hydrolysis of 32p-labelled dsRNA in 100 mM-NaHCO3 for 1 h at 100 °C (Nomoto & Imura, 1979;Kudo et al, 1991).…”
mentioning
confidence: 93%
“…1). These data showed that the 5' and 3' termini of the plus strands of all segments are adenine and cytidine, respectively, because the 3' termini of the plus strand of genome segments S 10 Uyeda et al, 1990), $8 and $7 (data not shown) were identified as cytidine by cDNA analysis. The nucleotide sequences of terminal regions of the genome were analysed by the wandering spot method (de Wachter & Fiers, 1972;Rensing & Schoenmarkers, 1973) after partial alkaline hydrolysis of 32p-labelled dsRNA in 100 mM-NaHCO3 for 1 h at 100 °C (Nomoto & Imura, 1979;Kudo et al, 1991).…”
mentioning
confidence: 93%
“…Other fijiviruses include maize rough dwarf (MRDV), rice black-streaked dwarf (RBSDV), pangola stunt (all belonging to serogroup 2), and oat sterile dwarf (serogroup 3). The nucleotide sequences of several genome segments from different fijiviruses belonging to serogroups 2 and 3 have been published (Uyeda et al, 1990 ;Marzachi et al, 1991 ;Azuhata et al, 1993). However, sequence data on FDV have been limited to primer sequences for use in PCR-based diagnostics (Smith et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the amino acid sequence identities between the major outer capsid proteins (MOCPs) range from 48 to 56 % (Omura et al, 1989;Xu et al, 1989;Noda et al, 1991 b). In the Fijivirus genus, the nucleotide sequences of MRDV genome segment 6 ($6) (Marzachi et al, 1991) and RBSDV S10 (Uyeda et al, 1990), $8 and $7 (Azuhata et al, 1993) have been reported, but those of their MOCPs are unknown. We previously reported the nucleotide sequence ofNLRV S10 (Noda et al, 1994).…”
mentioning
confidence: 99%
“…3. Comparison of the amino acid sequences of the predicted proteins encoded by NLRV $8 and RBSDV S10 (Uyeda et al, 1990). The sequences were aligned by the LFASTA program (Pearson, 1990) from the amino acid residues 7 to 522.…”
mentioning
confidence: 99%
See 1 more Smart Citation